Optimizing the Transaction with Customers Directions to Digital Transformation for Enterprises - Nguyen Thi Hang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The goods and service businesses are very concerned with customer information management and sales activities. Sales activities require high accuracy of information as well as good handling of sales operations. Data security requirements are essential for jobs in general and for online businesses in particular. Data must be protected so that only authorized personnel can review and edit. The paper uses qualitative research methods, system design analysis methods. Thereby, the article aims to clarify the stages of doing business activities in enterprises on the basis of applying digital technology platforms. The article shows how to build and deploy the B2B e-trading platform business model to connect customers with businesses. The article gives some solutions to support business operations of businesses. From there, helping the sales and business operations of the business to be effective, adapting to the context of digital transformation. The results of the article will create a communication channel and connection between two groups of objects in the market: customers and businesses. From there, it helps businesses get more information from customers to propose appropriate solutions to care for them, in order to improve the operational efficiency of the business.